The Effect of English Vocabulary Card Media on Improving Student Learning Achievement at SMAN 1 Tubaba - Labibah, Hasna Fitri (CV. Tripe Konsultan, 2023)
This study describes the urgency of using the English Vocabulary Card media. Card media contains pictures (objects, animals, and so on) that can train students and create vocabulary, these cards become instructions or stimuli for students to improve student learning outcomes. The purpose of the researchers conducting this research was to find out the increase in student learning outcomes using the English Vocabulary Card X media at SMAN 1 Tubaba. This research method uses a quantitative method using questionnaires, tests, and documentation instruments. The test was carried out 2 times, namely the pretest to find out the students' initial abilities, and the second test was the posttest to find out the results of the increase in student learning. The samples were taken using random sampling for class X SMAN 1 Tubaba. The results showed that there was an effect of using the English Vocabulary Card media on improving student learning outcomes based on the results of the pretest before using the English Vocabulary Card media, which was equal to 25% in the low category, after using the English Vocabulary Card media, students' grades could increase by 75% in the low category become high category.